Executive Dysfunction in Adolescents with Obesity: A Systematic Review - Landínez-Martínez, Daniel Alfredo; Arias-Valencia, Jhon Felipe; Gómez-Tabares, Anyerson Stiths (Psykhe, 2022)
Obesity has been linked to low cognitive performance throughout the human life span. Alterations relate to attention, memory, language, and executive function. However, the obesity-executive function association remains unclear in adolescents. This study presents a systematic review of executive function alterations in adolescents with obesity. A search equation was proposed (Executive dysfunction AND Obesity AND Adolescents), with sixty studies meeting the inclusion criteria in the Clarivate Analytics Web of Science Core Collection database. A bibliometric analysis was conducted to identify the importance of the research topic and a citation network was built to establish the lines of research. Finally, the citation network was exported to Gephi to visualize the research groups studying the topic. Findings suggest 4 lines of research: (a) structural and functional brain abnormalities in adolescents with obesity, (b) inhibitory control alterations in adolescents with obesity, (c) effects of physical and cognitive activity on the executive function of adolescents with obesity, and (d) working memory alterations in adolescents with obesity. Obese adolescents were found to prefer immediate rewards to long-term ones. Nevertheless, effective interventions increase the intake of fruit and vegetables and reduce that of calorie-dense food. The authors recommend additional longitudinal studies to assess whether executive function alterations are either a cause or a consequence of adolescent obesity.